A review of thermal management and innovative cooling strategies for data center - Nadjahi, Chayan; Louahlia, Hasna; Lemasson, Stéphane (Sustainable computing informatics and systems, 2018)
•Review of existing cooling technologies of data centers.•Analysis of energy consumption and energy savings of data centers.•Performance of various innovative future cooling technologies for high efficiency is studied. Within a data center, 52% of the electricity is used by the IT equipment, 38% by the cooling system, and 10% for the remaining equipment (electrical power distribution, UPS…). The cooling system is mandatory to maintain optimal air temperature and relative humidity and provide a safe environment for all the electronic equipment. This paper presents a review on thermal management in data centers and various potential cooling technologies developed respecting energy saving constraint. Numerous researchers have proposed different alternative cooling strategy and solutions to free air cooling. This article describes a state of the art cooling strategies of data centers. The open aisle configuration is the most often used technique to remove heat. It does not affect energy efficiency but increases the electricity consumption dedicated to air conditioning. The most promising cooling systems, capable of absorbing energy flux while decreasing electricity consumption and rising the energy efficiency, are identified and discussed. It includes free cooling, liquid cooling, two-phase technologies and building envelope.